Training on Making Teaching Materials in The Form of E-modules Based on Guided Discovery Learning for Teachers of Chemical MGMP Pesisir Selatan - Oktavia, Budhi; Guspatni, Guspatni; Fauzi, Ahmad (Pelita Eksakta, 2024)
Teachers stated that they wish to be able to produce learning materials and integrate a scientific approach into their implementation and use. Teachers recommend receiving training in the creation of ICT-based teaching materials in order to attain their innovative nature. As a result, we offer training activities to chemistry teachers who are members of the MGMP Chemistry Pesisir Selatan for the creation of teaching materials in the form of e-modules based on Guided Discovery Learning. Teachers will be given information on the main criteria of a teaching material (module), guided discovery learning, e-modules, visual and video editing with computer software, literacy, and other associated ICT skills during this activity.